2015
DOI: 10.1111/pbr.12336
|View full text |Cite
|
Sign up to set email alerts
|

SSRmarker development from peanut gynophore transcriptome sequencing

Abstract: Peanut is one of the most important oil crops in the world. To accelerate the marker‐assisted selection programmes of peanut, a transcriptome library of peanut gynophores at three different growth stages was constructed and sequenced using Illumina HiSeq™ 2000. Totally, 72 527 unigenes were assembled and mined for EST SSRs. A total of 5058 SSRs were obtained by using the SSR finding programme, which represented an average density of one SSR per 5.65 kb. Four thousand four hundred and forty‐two unigenes that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In the identified 12,765 SSR markers of A. miaotaiense , the major repeat type was di-nucleotide (2763, 24.72%) after the removal of the mono-nucleotide repeats, which was consistent with previous findings, followed by tri-nucleotide repeats (2362, 21.13%). The most dominant di-nucleotide repeat motif of A. miaotaiense was AG/CT (836, 7.48%), which was consistent with studies in peanut [ 61 ] and D. oliver [ 31 ], but the most abundant tri-nucleotide repeat motif was different from those of other plants (GAA/TTC for A. miaotaiense , AAG/CTT for D. oliver and AAG/CTT for peanut). In particular, the CG/CG motif was not observed in A. miaotaiense , which further supports the conclusion that the CG/CG repeat is rare in many dicotyledonous plants [ 62 , 63 , 64 ].…”
Section: Discussionsupporting
confidence: 85%
“…In the identified 12,765 SSR markers of A. miaotaiense , the major repeat type was di-nucleotide (2763, 24.72%) after the removal of the mono-nucleotide repeats, which was consistent with previous findings, followed by tri-nucleotide repeats (2362, 21.13%). The most dominant di-nucleotide repeat motif of A. miaotaiense was AG/CT (836, 7.48%), which was consistent with studies in peanut [ 61 ] and D. oliver [ 31 ], but the most abundant tri-nucleotide repeat motif was different from those of other plants (GAA/TTC for A. miaotaiense , AAG/CTT for D. oliver and AAG/CTT for peanut). In particular, the CG/CG motif was not observed in A. miaotaiense , which further supports the conclusion that the CG/CG repeat is rare in many dicotyledonous plants [ 62 , 63 , 64 ].…”
Section: Discussionsupporting
confidence: 85%
“…Currently, g-SSR markers are common and popular for such analyses, and they have wide applications in molecular genetics and breeding, because they have multiple advantages, such as simplicity, abundance, ubiquity, variation, co-dominance, and multi-allelism [28]. Recently, several studies were devoted to developing different types of SSR markers in peanut, such as EST-SSRs [11,29], transcriptome-SSRs [12][13][14], and g-SSRs [30], even though the peanut genome had not yet been resolved.…”
Section: Genome-wide Ssr Marker Developmentmentioning
confidence: 99%
“…SSRs derived from expressed sequence tags (ESTs), transcriptome sequences, and genomic DNA sequences are referred to as EST-SSRs, transcriptome-SSRs, and g-SSRs, respectively. In the past decade, several hundred EST-SSR markers were developed by investigating ESTs [10,11], and thousands of transcriptome-SSR markers were identified based on different transcriptome libraries of cultivated peanut [12][13][14]. Meanwhile, two integrated consensus genetic maps with thousands of different types of markers, such as EST-SSRs, transcriptome-SSRs, and g-SSRs, were constructed [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In bread wheat, it was shown that the polymorphism rate in EST-SSRs is lower than that in g-SSRs, suggesting that g-SSRs can serve as valuable complements to EST-SSRs and transcriptome-SSRs ( Balfourier et al, 2007 ; Han et al, 2015 ). A number of studies reported development of SSR markers in peanut, for example, EST-SSRs derived from cDNA libraries ( Liang et al, 2009 ; Song et al, 2010 ), SSRs from bacterial artificial chromosome (BAC)-end sequences ( Wang et al, 2012 ), and transcriptome-SSRs from a transcriptome library of developing seeds ( Zhang et al, 2012 ; Huang et al, 2016 ; Zhong et al, 2016 ; Zhou et al, 2016 ). Such studies were very limited and hence the available SSRs are insufficient for conducting moderate to high resolution genetic studies in peanut.…”
Section: Introductionmentioning
confidence: 99%